2008
DOI: 10.1172/jci33482
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoyl protein thioesterase-1 deficiency impairs synaptic vesicle recycling at nerve terminals, contributing to neuropathology in humans and mice

Abstract: Neuronal ceroid lipofuscinoses represent the most common childhood neurodegenerative storage disorders. Infantile neuronal ceroid lipofuscinosis (INCL) is caused by palmitoyl protein thioesterase-1 (PPT1) deficiency. Although INCL patients show signs of abnormal neurotransmission, manifested by myoclonus and seizures, the molecular mechanisms by which PPT1 deficiency causes this abnormality remain obscure. Neurotransmission relies on repeated cycles of exo-and endocytosis of the synaptic vesicles (SVs), in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
106
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 66 publications
12
106
0
Order By: Relevance
“…34 These results are also consistent with previous studies identifying potential presynaptic substrates of Ppt1 and its possible localization, which do not point to an interaction of Ppt1 with receptors or other post-synaptic targets. 26,41 Instead, most of the potential neuronal substrates, such as dynamin, SNAP25, CSP, VAMP2, syntaxin 1, SYTI, and GAD65, are pre-synaptic and control synaptic vesicle cycling. It is curious that the point mutation in the Ppt1 active site (Ppt1 A179T ) failed to modify mini EJP frequency.…”
Section: Alterations In Motor Functionmentioning
confidence: 99%
See 4 more Smart Citations
“…34 These results are also consistent with previous studies identifying potential presynaptic substrates of Ppt1 and its possible localization, which do not point to an interaction of Ppt1 with receptors or other post-synaptic targets. 26,41 Instead, most of the potential neuronal substrates, such as dynamin, SNAP25, CSP, VAMP2, syntaxin 1, SYTI, and GAD65, are pre-synaptic and control synaptic vesicle cycling. It is curious that the point mutation in the Ppt1 active site (Ppt1 A179T ) failed to modify mini EJP frequency.…”
Section: Alterations In Motor Functionmentioning
confidence: 99%
“…Though we have not yet examined synaptic vesicle numbers in Drosophila Ppt1-mutant nerve terminals, several groups have shown that loss of PPT1 in mouse cortical neurons in vitro results in a decline in the size of the readily releasable synaptic vesicle pool as well as the total vesicle pool. 25,26 Such changes in vesicle number are likely due to reductions in endocytosis, perhaps due to alteration in the function of dynamin and other palmitoylated presynaptic proteins. Indeed, consistent with in vitro mouse results, we have observed a significantly reduced ability of Ppt1 loss-of-function nerve terminals to recover from repetitive stimulation, as well as reductions in in vivo endocytosis measured by FM1-43 uptake (Fig.…”
Section: Alterations In Motor Functionmentioning
confidence: 99%
See 3 more Smart Citations